ANALISIS OVERREACTION HYPOTHESIS PADA SEKTOR PERUSAHAAN PROPERTI DAN KEUANGAN YANG GO PUBLIC DI BURSA EFEK INDONESIA - YUNITA, ELLYA (Universitas Katolik Widya Mandala Surabaya, 2012)
The capital market is a place where various commodities capital is traded as long-term instruments, one of which is a share. The most important thing to determine whether the trade would be ensued is the price. In addition, behaviours factor of the players in the capital markets can also encourage the formation of a price. Therefore, this research used the topic of overreaction hypothesis. This research aimed to find out if there is an overreaction phenomenon characterized by the existence of the reversal of the stock price of financial firms and properties in the Indonesia stock exchange in the period 2010-2011. This research used two portfolio which are portfolio winners and portfolio loser. Immensity overreaction measured by using average cumulative abnormal return portfolio, either on portfolio winners and portfolio loser. The technique used were One sample t-test and Paired sample t-test. The results show that there were some differences in the Average Cumulative Abnormal Return in each testing period, but not significantly so that portfolio winner remains the winner and the loser portfolio remains a loser. In general this means that the phenomenon of overreaction on the financial and property companies the period 2010-2011 was not found.